Patients’ and nurses’ perceptions and experiences of a digitally enabled cardiac telerehabilitation program—a qualitative study - Justin Braver; Tess Tsindos; Melinda J. Carrington; Catherine Keating; Darshini Ayton (BMC Digital Health)
Abstract Background Secondary prevention cardiac rehabilitation programs are paramount to prevent cardiovascular disease morbidity and mortality. However, they remain underutilized. Digital health programs provide an opportunity for healthcare delivery by breaking down access barriers. However, evidence for their implementation is lacking. Further evidence to ascertain the drivers for uptake and acceptance of digitally enabled cardiac telerehabilitation programs is required. Therefore, we aimed to explore the perceptions and experiences of patients, and their nurses enrolled in a digitally enabled cardiac telerehabilitation (DeCR) program, aiming to ascertain the drivers for program acceptance. Results 12 out of 52 participants and 2 cardiac nurses, from across Australia, who had completed a DeCR intervention, participated in semi-structured telephone interviews. Key benefits were personalised nurse telehealth consultations, education aimed at maintaining learned healthy behaviours and remote patient monitoring. However, digital connectivity was a challenge for patients. Nurses found that navigating administrative processes and establishing trust with patients were challenges in the absence of face-to-face care. Conclusion DeCR is well accepted by patients and their nurses. Remote monitoring in combination with personalised telehealth nurse consultations enhance patient-nurse communication and were key success factors in this model of care. Challenges with digital connectivity should be considered and addressed in future interventions. The challenges nurses face in delivering remote care is an important area that warrants further exploration. Further quantitative research is necessary to validate these findings. Trial registration ClinicalTrials.gov: NCT06813482, registered retrospectively on 07/02/2025.